Las verdades de Pero Grullo en periodismo - López de Zuazo Algar, Antonio (Estudios sobre el Mensaje Periodístico, 2007)
Perhaps Pero Grullo was a real person many years ago. Like a prophet or a prater. Francisco de Quevedo invent the word “perogrullada”, truism, in the 17th century. An italian Opera and a spanish weekly paper there was in the 18th century, when appear Grullo. A satirical newspaper and a Zarzuela, named “Pero Grullo”, there was in the 19th century. Many novelists, journalists and philologists mention the truism in the 20th century. There are three proverbs or adages: the poetical predictions, the evident truths and the lumpishness.